Influência da granulometria do resíduo de mármore e granito em compósitos poliméricos com fibras vegetais de sisal - REIS, Ingrid Moreira (2020)
With industrial development, the search for new materials that can replace conventional materials has become intense, thus creating an interest on the part of companies to invest in the quality of products in a sustainable and economic way. Based on these considerations, this paper aims to evaluate the influence of marble and granite residue particle size on sisal vegetable fiber polymer composites. The method used in this work was the hand lay up manufacturing process, where hybrid composites were made in the mass fraction of marble and granite residue of 5%, 10%, 15% and 20% and incorporated sisal fibers. in the 3% fraction. The residue was sourced from Brilasa Britagem e Laminando de Rochas S / A, which was manually sieved in a 100 and 200 mesh sieve. The fibers were supplied by the company SISALSUL, located in the state of São Paulo, which were manually cut to a length of 15 mm. The polymeric matrix used was the isophthalic polyester resin together with the cobalt accelerator (1.5% v / v) and the MEK-P catalyst (1% v / v). After making the plates, the specimens were obtained for each series manufactured for the physical characterization tests by apparent specific mass (ASTM D 792), water absorption (ASTM D 570) and apparent porosity (ASTM D 2734), in addition to the horizontal flammability (ASTM D 635) and tensile strength (ASTM D 3039) tests. Fracture surface analyzes were performed by scanning electron microscopy. The flammability test showed that the composites presented HB classification according to ASTM D 635 and met the specifications of CONTRAN / 2014, in which the load of 20% RMG / 3% FS in the 100 and 200 mesh size obtained a reduction of approximately 16% and 29%, respectively. In tensile tests there was an increase in strength, where the proportions of 5% RMG / 3% FS with 100 Mesh and 10% RMG / 3% FS with 200 Mesh obtained a resistance of approximately 22 MPa and 19 MPa, respectively. The morphological analyzes of the fracture surfaces were effective to determine the failure phenomena present in the materials, where the predominant mechanisms were ruptured fibers and the occurrence of pull-out of the matrix fiber.